Estratégia de obtenção e tratamento de dados digitais para elaboração de pesquisas de mobilidade urbana - Frederico Augusto da Silva (2021)
Cities have become large generators of digital data, but this information is neglected, as there is little or no processing and retrieval of this information. With the increase in the availability of digital data, combined with the use of Big Data techniques, new forms of acquisition emerge, whether for operational use or for long-term planning, transforming digital cities in such a way that they evolve to become smart cities. This dissertation presents a methodology for the acquisition and processing of information captured in electronic image surveillance equipment, arranged in the urban area of a municipality, for the creation of displacement matrices and better paths between the equipment in order to analyze the movement of vehicles in the road network. As a result, it was possible to identify the main paths taken, generating a traffic flow matrix throughout the city to support the development of urban mobility plans. In addition to the quantitative process, the work was evaluated by specialists in the area of traffic engineering, in order to validate the applied methodology. This work presents a case study, applying the entire methodology to the city of Belo Horizonte. This work contributes to traffic study research based on the collection of digital data and generates discussion for cities to realize the potential of the collected information.